Fixed-Life or Rechargeable Battery for Deep Brain Stimulation: Preference and Satisfaction in Chinese Patients With Parkinson's Disease - Qiu, Xian; Peng, Tingting; Lin, Zhengyu; Zhu, Kaiwen; Wang, Yuhan; Sun, Bomin; Ashkan, Keyoumars; Zhang, Chencheng; Li, Dianyou (Frontiers in Neurology, 2021)
Introduction：DBS is a widely used therapy for PD. There is now a choice between fixed-life implantable pulse generators (IPGs) and rechargeable IPGs, each having their advantages and disadvantages. The aim of this study is to evaluate the preference and satisfaction in the Chinese Parkinson’s disease (PD) patients treated with deep brain stimulation (DBS). Materials and Methods: Two hundred and twenty PD patients treated with DBS completed a self-designed questionnaire to assess long-term satisfaction and experience with the type of battery they had chosen, and the key factors affecting their choices. The survey was performed online and double-checked for completeness and accuracy. Results: The median value of follow-up length was 18 months. The most popular way for patients to learn about DBS surgery was through media (79/220, 35.9%), including the Internet and television programs. 87.3% of the DBS used rechargeable IPGs (r-IPG). The choice between rechargeable and non-rechargeable IPGs was significantly associated with the patient’s affordability (χ2(1) = 19.13, p < 0.001). Interestingly, the feature of remote programming significantly affected patients’ choices between domestic and imported brands (χ2(1) = 16.81, p < 0.001). 87.7% of the patients were satisfied with the stimulating effects as well as the implanted device. 40.6% of the patients with r-IPGs felt confident handling their devices within one week after discharge. More than half of the patients checked their batteries every week. The mean interval for battery recharge was 4.3 days. 57.8% of the patients spent around one-hour recharging, and 71.4% of them recharged the battery independently. Conclusions: Most patients were satisfied with their choices of IPGs. The patients' financial status and remote programming function were the two most critical factors in their decision. The skill of using rechargeable IPG was easy to master by most patients.